(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The research problem is evident in studying: What is the impact of financial incentives on the productivity of employees in the Education Department in Hafr Al-Batin Governorate? The study aimed to examine the financial incentive system in place in institutions and their role in improving employee performance. The objective limits of the study include its focus on knowing the impact of incentives, both material and moral, and their impact on employee productivity in the Education Department in Hafar Al-Batin as an example. The application of the study was limited to employees in the Education Department in Hafr Al-Batin Governorate during the year 2023-2024. The study relied on the descriptive correlational approach to determine the level of material incentives and their impact on the productivity of employees in the Education Department in Hafr Al-Batin. The study population consists of employees of the Education Department in Hafr Al-Batin Governorate, while the target study sample consists of employees whose number ranges from (228) employees. The study found that responses are statistically distributed according to relative strength (68.70%). The study recommends that the standard for evaluating employees’ performance be the standard of reward and punishment within the work environment, so that the use of incentives, whether positive or negative, against employees comes in a way that ensures achieving the goals of the incentive system.